Glass Microspheres 90Y Selective Internal Radiation Therapy and Chemotherapy as First-Line Treatment of Intrahepatic Cholangiocarcinoma. (November 2015) - Edeline, Julien; Du, Fanny Le; Rayar, Michel; Rolland, Yan; Beuzit, Luc; Boudjema, Karim; Rohou, Tanguy; Latournerie, Marianne; Campillo-Gimenez, Boris; Garin, Etienne; Boucher, Eveline
Abstract : Purpose of the Report: Intrahepatic cholangiocarcinoma's incidence is increasing. We studied the efficacy of 90 Y selective internal radiation therapy (SIRT) as first-line treatment, with chemotherapy, and compared with the results of chemotherapy alone. Patients and Methods: We retrospectively studied data from patients treated at our institution with glass microspheres SIRT for intrahepatic cholangiocarcinoma as part of first-line treatment in combination with chemotherapy. We compared results with those of similar patients treated in the ABC-02 study (a study in advanced biliary tract cancer that defined the current standard chemotherapy), assessed as not progressing after the first evaluation. We assessed progression-free survival (PFS) and overall survival (OS). Results: Twenty-four patients were treated with SIRT. Chemotherapy was given concomitantly in 10 (42%), as induction before SIRT in 13 (54%) or after SIRT in 1 (4%). Grade 3 adverse events were reported in 1 (4%). Median PFS after SIRT was 10.3 months. Longer PFS was observed when chemotherapy was given concomitantly than when chemotherapy was given before SIRT, with respective median of 20.0 versus 8.8 months ( P = 0.001). Median OS after SIRT was not reached. Eleven patients went to surgery (46%). Thirty-three patients in ABC-02 had locally advanced nonextrahepatic cholangiocarcinoma, not progressing after first evaluation. From the start of any treatment, the median PFS was 16.0 months in our cohort versus 11.3 months in ABC-02 ( P = 0.25), whereas the median OS was significantly higher in our cohort, not reached versus 17.9 months, respectively ( P = 0.026). Conclusions: Selective internal radiation therapy combined with concomitant chemotherapy seems a promising strategy as first-line treatment for unresectable intrahepatic cholangiocarcinoma. Abstract : Supplemental digital content is available in the text.